Evaluating the Therapeutic Efficacy of Si-Wu-Tang Decoction and Concentrated Extract in Follicular Maldevelopment-Related Menstrual Disorders Through Pharmacokinetic/Pharmacodynamic Studies - Lee, Chia-Jung; Kapelemera, Alinafe Magret; Tsai, Yi-Zhe; Lee, Ching-Tzu; Xu, Ming-Yi; Wang, Ching-Chiung (Frontiers in Pharmacology, 2020)
Si-Wu-Tang (SWT), a traditional Chinese formula, is commonly used to relieve menstrual discomfort and climacteric syndrome. Water decoction (WD) and concentrated herbal extract (CHE) are the two most common formulations of traditional Chinese medicine (TCM). However, few studies have reported the equivalency of these two formulations. In this study, 23 healthy volunteers were included to determine the pharmacokinetic (PK) equivalent dosage of WD and CHE, and 25 infertile women with follicular maldevelopment to evaluate the pharmacodynamic (PD) effects on menstrual disorders. The randomized, two-way crossover comparative PK study of SWT-WD and SWT-CHE analyzed the active component, ferulic acid. The results showed that clinical doses of 170 mL SWT-WD and 18 g SWT-CHE produced the same amount of ferulic acid in the blood. The PD study showed that patients who took both of these formulations had an initial luteinizing hormone/follicle-stimulating hormone ratio of <1; however, the value returned to normal and their symptoms all improved after taken SWT. Our results showed that WD and CHE, both prepared from 40 g of SWT, displayed bioequivalence upon PK/PD analysis.